Probabilistic Risk Assessment of Electric Power Infrastructure Subjected to Earthquake-Induced Landslides - Jampole, Ezra; ICASP14; Kenawy, Maha (My University, 2023)
We develop a probabilistic framework to assess the vulnerability of electric power transmission structures to shallow landslides induced by earthquake ground shaking. We probabilistically describe possible damage states of transmission pole structures that may be induced by differential ground movement during landslide events, as a function of their configuration, material properties, and connectivity to electrical overhead conductors. We integrate the fragilities of the structures with the earthquake-induced landslide displacement hazard, which is predicted based on the geotechnical site properties using a Newmark sliding block model, and the seismic hazard at the site obtained via probabilistic seismic hazard analysis. Accordingly, we predict annual rates of failure based on the deformation of the structures due to ground movement. The framework is implemented at a regional scale utilizing the U.S. Geological Surveyﾒs seismic hazard disaggregation tool and the underlying U.S. National Seismic Hazard Map to quantify the risks to electric power infrastructure due to earthquake-induced landslide hazards.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED